Revisiting Marx's Theory of Crisis during the Covid-19 Pandemic - Shang Li (New proposals, 2023)
The Covid-19 pandemic has caused millions of deaths and the most devastating economic crisis since the Great Depression. Although it seems clear and straightforward to regard the current capitalist crises as the direct result of external destructive factor, this interpretation does not touch on the internal essence of the capitalist mode of production, nor can it explain the recurrence of crises throughout the history of capitalism. By contrast, this paper analyses the three dimensions, possibility, necessity and reality, in Marx’s theory of crisis, demonstrates that the capital accumulation is an internally contradictory process and that the process has been accelerated by time-space compression, and argues that the current economic crisis is the result of the virus passing through the accelerated capital accumulation rather than the virus by itself